Evaluación preliminar de la Variabilidad de la Frecuencia Cardiaca de Pacientes con Fibrilación Auricular Paroxística y Apnea Obstructiva - Becerra Luna, Brayans; Escobar-Alvarado, Jennifer; Martínez-Memije, Raúl; Sánchez Espinosa de los Monteros, Veronica; Gómez-Flores, Jorge Rafael; Infante-Vázquez, Oscar (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
This paper describes the processing of electrocardiographic (ECG) signals from 16 patients diagnosed with paroxysmal atrial fibrillation and sleep apnea-hypopnea syndrome (SAHS) classified as either moderate or severe by respiratory polygraphy. Processing goes from acquisition up to the analysis of their heart rate variability (HRV), where original computer scripts written in MATLAB R2020b are used within scripts adapted from other research groups. Computer processing included linear resampling, noise suppression, R-wave detection, misidentified peaks correction, tachogram resampling at a constant period and trend removal. Regular sampling is mandatory for Fourier analysis through Welch’s periodogram. Once the spectral power was estimated, the HRV was evaluated before, during and after an apnea episode. The behavior of the HRV was compared to the group of patients with moderate SAHS against those with severe SAHS. When comparing the groups at post-apnea stage, significant differences were found in the normalized low-frequency band (LF: 0.04–0.15Hz, p=0.0183), and also in the normalized high frequency band (HF: 0.15–0.4 Hz, p=0.0182), which suggests that in patients with severe SAHS the sympathetic activity is higher (power in LF band), which in turn presupposes that the autonomic nervous system is in frequent alertness, which has been associated with high cardiovascular risk.